PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PMR PADA POKOK BAHASAN JAJARGENJANG DAN BELAHKETUPAT - Shoffan Shoffa (Universitas Muhammadiyah Surabaya, 2009)
ABSTRACTIONOne of [the] important characteristic [of] mathematics [is] to have abstraction obyek, so that still many student assume that mathematics [is] difficult. Nature of the abstraction represent one of [the] difficult cause [of] him a student comprehend school mathematics. For that, in study of mathematics, besides comprehending items, student also requireto understand the way of mathematics items application in life of reality.This research represent research of development with aim to to develop peripheral of study of Mathematics with Approach Of PMR [At] Fundamental Discussion of Jajargenjang and of Belahketupat.Development of peripheral relate [at] model 4-D (model of Thigarajan, and semmel of semmel) that is definition phase, scheme phase, and development phase. For the phase of desiminasi not yet been [done/conducted] [by] because this phase refer [at] usage of peripheral of study which have been developed [by] [at] broader scale, for example[in] other class, other school, by other teacher. Limited test-drive [done/conducted] [by] [at] 30 class student of VII D SMP N 4 Babat Lamongan